Effects of Crude Red Fruit (Pandanus conoideus Lamk.) Oil Concentrations on Physicochemical, Total Carotenoids, and Organoleptic Characteristics of Mayonnaise - Yantewo, Ester Papuany; Sarungallo, Zita Letviany; Santoso , Budi; Epriliati, Indah (Journal Akademik Universitas Swiss German, 2024)
Red fruit (Pandanus conoideus) oil (RFO) which provides high antioxidant as well as having unique aromas is potential use as a functional ingredient for functional food product developments, e.g., mayonnaise. The present research aimed to determine the effects of RFO and water concentration on physical and organoleptic properties, and total carotenoids contributed by RFO in mayonnaise formulas. The methods comprised of 4 mayonnaise formulas with RFO:water ratios coded F1 (25:45), F2 (20:50), F3 (15:55), and F4 (10:60); while other ingredients, i.e., egg yolk of 5,5%, starch 5%, CMC 1%, citric acid 1%, acetic acid 4%, sugar7,5%, and mustard 3%. Parameters observed were colour, viscosity, emulsion stability, and organoleptic; moisture and carotenoid content. Results indicated that all formulas were in the ranges of dark reddish orange to orange in colour, had a specific RFO aroma and mildly acid, viscosity (200 – 240 dPoise), the emulsion were stable for between 3-7 days stored at room temperature. Organoleptic scores for all formulas obtained 4.66 – 5.92 (slightly liked to liked) for colour, 4.33 -5.25 (slightly liked to liked) for aroma, 4.14–4.96 (neutral to slightly liked) for taste, 5.51-5.70 (slightly liked to liked) for smoothness and for overall scores were 4.85-5.51 (slightly liked to liked). The best formula was F2 obtained from composition of RFO:water 20:50, with color pale reddish-orange, viscosity of 205 d.Poise, stable for 8 days, 57.75% (w/w) for moisture, and total carotenoids 2.550 ppm